Bifunctional Ni1−xFex layered double hydroxides/Ni foam electrodes for high-efficient overall water splitting: A study on compositional tuning and valence state evolution. (23rd February 2017) - Liu, Qingyun; Wang, Hao; Wang, Xina; Tong, Rui; Zhou, Xiaolong; Peng, Xiaoniu; Wang, Hanbin; Tao, Hualong; Zhang, Zhihua
Abstract: Toward both hydrogen (HER) and oxygen evolution reaction (OER) in alkaline electrolyte, bifunctional Ni1−x Fex layered double hydroxides (LDHs) on Ni foam (NF) have been systematically developed for high-efficient water splitting by changing Fe content. The interlaced NiFe LDHs nanosheets consist of ultra-small γ-NiOOH-like nanoparticles with size of 2–5 nm interconnected by amorphous domains. By tuning Fe content from 15% to 25% and 36%, optimized μ10 values (μ10 is the overpotential required to reach a current density of 10 mA/cm 2 ) of 169 mV (HER) and 140 mV (OER), and Tafel slope of 31 mV/dec have been achieved at x = 0.25. A hydrogen generation rate of 170 μmol/h/cm 2 with H2 /O2 ratio nearly to 2:1 and Faradic efficiency of 93% have been realized at 1.7 V by using two Ni0.75 Fe0.25 LDHs/NF as respective anode and cathode in a 2-electrode system. Based on the valence state evolution of the electrodes, undergoing respectively H2 and O2 generation, tremendous transformation of NiFe(OH)2 to NiFeOOH is deduced, which reaches a Ni 3+ /Ni 2+ ratio of ∼2.35 for the Fe content of 25%. Further or less Fe incorporation will depress the electrocatalytic property. The effective Ni 3+ active sites on the NiFe-based nanosheets endow the Ni0.75 Fe0.25 LDHs/NF with high bifunctional catalytic property. Highlights: Ni1−x Fex LDHs/Ni foam electrodes with excellent bifunctional water splitting performance were fabricated by tuning Fe content. Optimum overpotentials of 169 mV (HER) and 140 mV (OER) were achieved for Ni0.75 Fe0.25 LDHs/NF to reach 10 mA/cm 2 . A hydrogen generation rate of 170 μmol/h/cm 2 with a nearly 2:1 H2 /O2 ratio was established at 1.7 V in two-electrode system. Fe content-dependent NiFe(OH)2 –NiFeOOH transformation was deduced from XPS study to address the bifunctional property.